Long-term performance of subcutaneous implantable defibrillators in athletes: a multicenter, real-world analysis of sport activities from the iSUSI registry - Gasperetti, Alessio; Schiavone, Marco; Vogler, Julia; Compagnucci, Paolo; Laredo, Mikael; Breitenstein, Alexander; Gulletta, Simone; Martinek, Martin; Kaiser, Lukas; Lavalle, Carlo; Gaine, Sean; Santini, Luca; et al. (Heart rhythm, 2025)
Background - No data regarding subcutaneous-implantable cardioverter defibrillator (S-ICD) technology in patients actively engaging in sports activities are available. - Objective - This study aims to compare S-ICD performance between athletes and nonathletes. - Methods - The primary outcome of the study was the comparison of overall device-related complications between athletes and nonathletes. Appropriate shocks, inappropriate shocks, and individual device-related complications were secondary outcomes. - Results - A total of 1493 patients were extracted from the International Subcutaneous Implantable Cardioverter Defibrillator Registry (iSUSI) registry, of whom 152 (10.2%) were athletes, mostly engaging in dynamic sports (54.2%). Brugada syndrome, myocarditis, and arrhythmogenic right ventricular cardiomyopathy (ARVC) were more common in athletes (11.2% vs 3.3%, P < .001; 19.1% vs 9.0%, P < .001; 8.6% vs 2.8%, P < .001, respectively). During a median follow-up time of 25.5 (12.0-41.2) months, athletes were more likely to experience appropriate shocks (yearly rate: 7.2 [4.9-10.7] % vs 4.3 [3.6-5.1] %, P = .028), occurring more frequently during exercise (3.9% vs 0.6%, P < .001). This finding lost significance when adjusting for confounders (adjusted hazard ratio [aHR] 1.440 [0.909-2.281], P = .120). No differences were found in overall device-related complications (yearly rate: 3.3% vs 3.4%, P = .448) and inappropriate shocks (yearly rate: 5.3% vs 3.7%, P = 0.111). Myopotential oversensing (4.0% vs 1.3%, P = .011) was more common in athletes, as were lead infections (3.3% vs 0.9%, P =.008), with the latter clustering in the early postimplantation period. - Conclusion - The S-ICD is a valid therapeutic option for preventing sudden cardiac death in athletes. Sports practice was not associated with an increased risk of complications or inappropriate shocks, although athletes are exposed to a higher risk of S-ICD infections in the early postoperative period.
Online verfügbar: 20. September 2024, Artikelversion: 1. Juli 2025
Gesehen am 11.11.2025